Hibernation and hemostasis - De Vrij, Edwin L.; Bouma, Hjalmar R.; Henning, Robert H.; Cooper, Scott T. (Frontiers in Physiology, 2023)
Hibernating mammals have developed many physiological adaptations to accommodate their decreased metabolism, body temperature, heart rate and prolonged immobility without suffering organ injury. During hibernation, the animals must suppress blood clotting to survive prolonged periods of immobility and decreased blood flow that could otherwise lead to the formation of potentially lethal clots. Conversely, upon arousal hibernators must be able to quickly restore normal clotting activity to avoid bleeding. Studies in multiple species of hibernating mammals have shown reversible decreases in circulating platelets, cells involved in hemostasis, as well as in protein coagulation factors during torpor. Hibernator platelets themselves also have adaptations that allow them to survive in the cold, while those from non-hibernating mammals undergo lesions during cold exposure that lead to their rapid clearance from circulation when re-transfused. While platelets lack a nucleus with DNA, they contain RNA and other organelles including mitochondria, in which metabolic adaptations may play a role in hibernator’s platelet resistance to cold induced lesions. Finally, the breakdown of clots, fibrinolysis, is accelerated during torpor. Collectively, these reversible physiological and metabolic adaptations allow hibernating mammals to survive low blood flow, low body temperature, and immobility without the formation of clots during torpor, yet have normal hemostasis when not hibernating. In this review we summarize blood clotting changes and the underlying mechanisms in multiple species of hibernating mammals. We also discuss possible medical applications to improve cold preservation of platelets and antithrombotic therapy.